Kebijakan Luar Negeri Amerika Serikat: Perjanjian Damai dengan Taliban Tahun 2020 - Awani Yamora Masta (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2022)
The events of 9/11 of 2001 led the United States to issue a Global War on Terror (GWOT) policy. One implementation of this policy is the war against Al-Qaeda groups under the Taliban regime in Afghanistan. The U.S. has launched several attacks against the Taliban, killing many U.S. soldiers and civil society in the region. After decades of fighting the Taliban with military force, the U.S. ultimately signed a peace treaty with the Taliban on February 29, 2020. Although the U.S. military is still at the forefront of warfare, it chooses to use a lenient approach to its war opponents. This research aims to determine the factors influencing the United States to enter a peace agreement with the Taliban in 2020. The theory used is the decision-making theory. This research will use the qualitative research method and data from scientific writings and credible news that discuss related or similar topics. The findings in this research imply that three factors impacted the peace agreement with the Taliban signed by The U.S. in 2020. They are domestic politics, economic and military capacity, and international context.